2012
DOI: 10.1007/s00406-012-0321-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of a mineralocorticoid receptor gene functional polymorphism in the symptom dimensions of persistent ADHD

Abstract: Attention-deficit/hyperactivity disorder (ADHD) affects approximately 5 % of school-aged children and 2.5 % of adults. Genetic studies in ADHD have pointed to genes in different neurobiological systems, with relatively small individual effects. The mineralocorticoid receptor is the main receptor involved in the initial triggering of stress response. Therefore, its encoding gene (NR3C2) is a candidate for psychiatric disorder studies, including ADHD, and behavioral phenotypes. There is evidence that the Val all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…These are showed in Supplementary Table 1. 35, 48, 53, 54, 57, 60, 64, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, 111, 112, 113 In particular, among the most known, DRD5 , whose highly polymorphic dinucleotide repeat (CA) n has been the most studied in adults, three studies 54, 60, 80 were available, but Squassina et al 80 was excluded because no frequencies were reported. Ribases et al 48 investigated other polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…These are showed in Supplementary Table 1. 35, 48, 53, 54, 57, 60, 64, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, 111, 112, 113 In particular, among the most known, DRD5 , whose highly polymorphic dinucleotide repeat (CA) n has been the most studied in adults, three studies 54, 60, 80 were available, but Squassina et al 80 was excluded because no frequencies were reported. Ribases et al 48 investigated other polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…[Since the submission of the manuscript, a recent casecontrol study reported an association between the NR3C2 rs5522 SNP and symptoms of inattention and hyperactivity, with P between 0.01 and 0.05 (Kortmann et al 2012). This association was not replicated in the current study, when the number of inattention and hyperactivity items of the CBCL was used as quantitative traits in the FBAT analysis.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, these genetic factors have not been investigated in the context of ADHD. [Since the submission of the manuscript, a study by Kortmann and colleagues reported an association between the NR3C2 rs5522 SNP and symptoms of inattention and hyperactivity, with P between 0.01-0.05 (Kortmann et al 2012). This study compared adult patients with ADHD, n = 478, to healthy controls, n = 597].…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, it was shown that such allele increases salivary and plasma cortisol responses to psychosocial stressor and dexamethasone suppression test (van Leeuwen et al, 2011). The NR3C2 rs5522-Val allele was also linked to severity of attention-deficit/hyperactivity disorder (Kortmann et al, 2013), depressive symptoms in geriatric patients (Kuningas et al, 2007) and altered reward learning (Bogdan et al, 2010). Additionally, a genome wide association study (GWAS) has found a nominal association between NR3C2 rs5522 SNP and severity of smoking behavior (P ¼ 1.52EÀ05), with the Val allele increasing the number of smoked cigarettes per day (Berrettini et al, 2008).…”
Section: Introductionmentioning
confidence: 98%